2015
DOI: 10.1080/00071668.2015.1008994
|View full text |Cite
|
Sign up to set email alerts
|

Variation in the chickenLPIN2gene and association with performance traits

Abstract: The objective of the study was to investigate the distribution of LPIN2 variants and haplotypes among breeds and perform an association analysis of the variants and haplotypes with the broiler traits in chickens. Six breeds were used to study the variation and distribution of chicken LPIN2, and an F2 resource population was used to measure growth traits, carcass traits, meat quality traits and serum biochemistry parameters. A c.-599G>A variant was located in the promoter region of LPIN2 and c.444G>A and c.1730… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…A previous study has mapped GLU traits elsewhere on GGA17 [25]. In addition, a total of 23 QTLs on different chromosomes have been associated with GLU levels in studies based on different experimental designs [13,[25][26][27][28][29][30]. For example, Hee-Bok Park et al performed QTL analysis on an F2 population with 874 individuals composing 75 full-sib families and found that one QTL on GGA20 at the 41 Mb site and one QTL on GGA27 at the 21 Mb site were related to the GLU trait [28].…”
Section: Discussionmentioning
confidence: 99%
“…A previous study has mapped GLU traits elsewhere on GGA17 [25]. In addition, a total of 23 QTLs on different chromosomes have been associated with GLU levels in studies based on different experimental designs [13,[25][26][27][28][29][30]. For example, Hee-Bok Park et al performed QTL analysis on an F2 population with 874 individuals composing 75 full-sib families and found that one QTL on GGA20 at the 41 Mb site and one QTL on GGA27 at the 21 Mb site were related to the GLU trait [28].…”
Section: Discussionmentioning
confidence: 99%